Increment in eucalyptus diameter as affected by seasonality and production system - Tonini, Helio; Morales, Mariana Moura; Magalhaes, Ciro Augusto de Souza; Silva, Vanderley Porfirio da (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to assess the current monthly increment in diameter of eucalyptus (Eucalyptus grandis x Eucalyptus urophylla) trees in response to different production systems, climatic factors, and thinning. The trees were evaluated in four production systems: monoculture and crop-forestry, livestock-forestry, and crop-livestock-forestry integration. The increment in diameter of 80 trees was measured monthly from May 2015 to May 2019. The effect of the climatic variables was determined through correlation and multiple regression analyses. The increment in current monthly diameter is seasonal and highly dependent on accumulated rainfall. The adopted modeling allowed concluding that both water shortage and excess (30 and 475 mm per month, respectively) decreased tree growth in diameter. The trees in the integrated systems showed a higher growth in diameter than those under monoculture, and intercropping with crops resulted in a greater diameter growth than that with pasture. Thinning accelerates the growth of the remaining trees, with an effect of higher magnitude and longer duration in the integrated production systems.